A STUDY OF EMOTIONAL INTELLIGENCE OF ADOLESCENTS IN RELATION TO MODERNIZATION - Sharma, Anamika; Singh, Ashwarya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The objective of the study was to compare the intrapersonal awareness, interpersonal awareness, intrapersonal management, interpersonal management and emotional intelligence of adolescent boys and girls in relation to their modernization. With the use of descriptive method, the researcher collected the data on a random sample of 150 adolescent students. This study was conducted on the adolescent students who were studying in the secondary schools of Raipur and Sahaspur blocks of district Dehradun. Emotional intelligence was taken as dependent and modernization was taken as the independent variable. Emotional Intelligence Inventory and Modernization Scale were used to collect the data. Analysis of variance was computed to analyze the data. Findings showed that there is a significant difference in the intrapersonal awareness, interpersonal awareness, intrapersonal management, interpersonal management as well as total emotional intelligence of the adolescent boys and girls in relation to their modernization. It has been found that adolescent boys who had high and average modernization had very poor emotional intelligence but those boys who had low modernization have average emotional intelligence. On the other hand, adolescent girls who had average and low modernization had very poor emotional intelligence but those girls who had high modernization had poor emotional intelligence.